Cloning, expression and toxicity of a mosquitocidal toxin gene of Bacillus thuringiensis subsp. medellin - RESTREPO, NORA; GUTIÉRREZ, DIANA; PATIÑO, MARÍA MERCEDES; THIÉRY, ISABELLE; DELÉCLUSE, ARMELLE; ORDUZ, SERGIO (Revista Colombiana de Entomología, 1997)
Bacillus thuringiensis (Bt) subsp. medellin (Btmed) produces parasporal crystalline inclusions that are toxic to mosquito larvae. It has been shown that the inclusions of this bacterium contain mainly proteins of 94, 68, and 28-30 kDa. EcoRI partially digested total DNA of Btmed was cloned by using the Lambda Zap II cloning kit. Recombinant plagues were screened with a mouse policlonal antibody raised against the 94 kDa crystal protein of Btmed. One of the positive plagues was selected, and by in vivo excision, a recombinant pBluescript SK(-) was obtained. The gene encoding the 94 kDa toxin of Btmed DNA was cloned in a 4.4 kb DNA fragment. Btmed DNA was then subcloned as a EcoRI/EcoRI fragment into the simule vector pBU4 producing the recombinant plasmid pBTM3 and used to transform by electroporation Bt subsp. israelensis (Bti) crystal negative strain 4Q2-81. Toxicity to mosquito larvae was estimated by using first instar laboratory-reared Aedes aegypti, and Culex quinquefasciatus larvae challenged with whole crystals. Toxicity results indicate that the purified inclusions from the recombinant Bti strain were toxic to all mosquito species tested, although the toxicity was not as high as the one produced by the crystal of the Btmed wild type strain. Poliacrylamide gel electrophoresis indicates that the inclusions produced by the recombinant strain Bti (pBTM3) were mainly composed of the 94 kDa protein of Btmed, as it was determined by Western blot.